The role of leadership strategies in building market orientation in the telecommunications sector - Warya Najm Rashid (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
Entrepreneurship strategies are important strategies that drive organizations to meet the desires and needs of customers, as well as access to unique. The data collected through survey questionnaire, from (57) managers in the number of the Internet Companies in Slemani governorate. A set of statistical tools have been used to analyze the data through (SPSS V.21). The results found that there is a positive relationship between entrepreneurship strategies and market orientation; in addition the entrepreneurship strategies have a positive effect in general in building market orientation. Finally, set of conclusions were indicated which would assist to present a number of recommendations, the most important one is Internet companies need to using entrepreneurship strategies to build market orientation.